PENGARUH EASE OF USE DAN E-WOM TERHADAP KEPUTUSAN PEMBELIAN SECARA ONLINE MELALUI LIFESTYLE PADA E-COMMERCE SHOPEE - Pratiwi, Desinta (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2021)
The purpose of this study is to analyze the influence of Ease of Use and Electronic Word of Mouth (E-WOM) to the lifestyle as well as its impact on purchase decision of Shopee customer in Surakarta. The population in this study are Shopee users in the city of Surakarta and the sample size using SEM analysis tools is 100-200. Analysis techniques using Structural Equation Model (SEM). The result of this study show that the Ease of Use and E-WOM have influence on lifestyle. E-WOM have influence on purchase decision but different with Ease of Use have no significant on purchase decision. In conclusions, the lifestyle is an intervening variables that can mediate the effect of variable Ease of Use and E-WOM on purchase decision. Keywords : Ease of Use, E-WOM, Lifestyle, and Purchase Decision.